Development Counting Box In Mathematics Subjects for Grade I Elementary School Students - Hilmi Manbaul Hikam; Mukni'ah Mukni’ah; Umi Farihah (Journal of Educational Sciences, 2026)
Mathematics learning requires learning media as a supplement because it is difficult to understand only through books. This study developed counting box media for first grade students at MI Miftahul Ulum Sampangan Muncar Banyuwangi with the following research questions: 1) How is the counting box media developed? 2) How feasible is this media? Therefore, the researcher took the title "Development of Media Counting Box in Mathematics Subjects in Mathematics Subjects for Grade 1 Students of MI Miftahul Ulum Sampangan Muncar Banyuwangi. This study uses the Research and Development (R&D) method with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data used are qualitative and quantitative data. The results of the study show that the counting box learning media meets the feasibility criteria from expert testing. Media expert validation reached 94%, material experts 91%, and learning experts 98%. The overall average percentage of expert validation was 94% with valid qualifications and feasible for use as mathematics learning media in grade 1 at MI Miftahul Ulum Sampangan Muncar Banyuwangi.